GLDC interacts with VPS34 to inhibit tumorigenesis and epithelial-mesenchymal transition in hepatocellular carcinoma - Zan Song; Hao Dong; Kailing Zhang; Bingke Qiao; Leilei Li; Zhicheng Zhang; Zhili Fan; Jing Li; Yu Li; Mengfei Liu; Ying Liu; Xinyu Gu; et al. (Pharmaceutical Science Advances)
Hepatocellular carcinoma (HCC) accounts for 90% of primary liver cancer with high mortality and limited therapeutic strategy. Glycine decarboxylase (GLDC) is the key limiting enzyme in glycine breakdown metabolism and acts as oncogene or tumor suppressor to impact tumor onset and progression in a context dependent manner. However, the underlying mechanism of GLDC on autophagy and progression is largely unexplored in HCC. Here, we showed that GLDC overexpression inhibited cell proliferation, cell migration and promoted cell senescence and autophagy in HCC. Intriguingly, induced GLDC remarkably attenuated epithelial-mesenchymal transition (EMT) progress and tumor growth in vitro and in vivo. Mechanically, we demonstrated that GLDC upregulated VPS34 protein and enhanced its interaction with VPS34, thus promoting the association of VPS34 with Beclin1/ATG14 complex and autophagy induction in HCC. Importantly, GLDC acetylation at K514 promoted interaction of GLDC-VPS34, whereas GLDC acetylation-dead mutant K514R abolished their binding. Furthermore, GLDC protein was decreased in HCC tissues compared with para-tumor tissues and reduced GLDC was significantly correlated with poor prognosis of patients. In conclusion, we unveil the key regulatory role of GLDC in autophagy and HCC progression through VPS34 and provide a potential strategy for HCC therapy.